Codificando o alfabeto por meio do sistema de numeração binário - Almeida, Meire Aparecida de (2013)
The main objective of this work is to report a didactic experience with activities different of the commonly used in school activities. Stands out the importance of linking the mathematical content with the daily affairs of the students. By observing the students' disinterest in learning math, the many questions about where they could use the knowledge learned in school in their everyday life, and by observing the difficulty that students often have in understanding the formation of a numbering system, we designed a work exploring the binary numbering system. As it is very present in the technologies, which we no longer can avoid, and for being a structured system like all others, differing only by the base used, he became the focus of the study. The binary numbering system was introduced to the students through practical activities that aroused the curiosity of them about the possibility of writing numbers and letters using only the digits 0 and 1.